Heart failure with preserved ejection fraction (HFpEF) is associated with cognitive impairment and reduced brain volume: Human neuropathology/vascular. (7th December 2020) - Hugenschmidt, Christina E.; Hughes, Timothy M.; Jung, Youngkyoo; Lockhart, Samuel N.; Whitlow, Christopher T.; Yang, Mia; Williams, Benjamin J.; Cleveland, Maryjo; Bateman, James R.; Baker, Laura D.; Sachs, Bonnie C.; Craft, Suzanne; et al.
Abstract: Background: Increasingly, vascular diseases are implicated in risk for Alzheimer's disease and related dementias. Heart failure (HF) with preserved ejection fraction (HFpEF) is the most common form of HF in the U.S and most commonly affects older women with overweight/obesity. Given known systemic microvascular effects of HFpEF, dementia risk may be a potential unrecognized downstream effect of the disease. Method: Harmonized cognitive testing and brain MRI protocols were employed in Wake Forest's Alzheimer's Disease Research Center's Clinical Core and the SECRET‐2 clinical trial of HFpEF. Cognitive tests included components of NACC's Uniform Data Set version 3. Brain imaging protocols included structural MRI and cerebral blood flow images. Statistical comparisons of cognitive and imaging data by cognitive/group status were done using multivariable general linear models adjusting for basic covariates including age, race, and sex in basic models and additional adjustments for intracranial volume (for MRI) and education (for cognitive test scores) in fully adjusted models using SAS 9.4. Result: The analysis includes a comparison of 89 participants recruited into the Wake Forest ADRC (adjudicated as cognitively normal, n=43; MCI, n=22; and dementia, n=5) and SECTRET‐2 intervention trail in HFpEF (n=19) patients. Compared to cognitively normal participants, patients with HFpEF were significantly more likely to be Black (47% vs 2%, p<0.01), have a higher body mass index (38.2 vs. 28.0, p<0.01), and a diagnosis of hypertension (84% vs 26%). Patients with HFpEF had poorer global cognitive performance [MoCA score, beta(SE)=‐1.76(0.77), p=0.02)], but no differences in Craft Story delayed recall in models adjusted for age, gender, race and education. HFpEF was also significantly associated with smaller gray matter volume [beta(SE)=‐20.7(11.6), p=<0.01)] at levels worse than MCI and dementia in models adjusted for age, gender, race and ICV. No initial differences were observed in resting cerebral blood flow or evoked cerebrovascular response due to hypercapnia. Conclusion: HFpEF participants showed deficits in global cognitive function that were comparable to those with MCI, as well as global decreases in brain volume. Additional follow‐up of these participants with HFpEF will more deeply phenotype cognitive impairments by domain and adjudication criteria used for MCI and dementia.